DAMPAK KEBIJAKAN PELAYANAN TERPADU SATU PINTU ON MALL DI KOTA MANADO - HUSEIN, MOHAMMAD AGUNG; PANGKEY, MASJE; LALOMA, ALDEN (Sam Ratulangi University, 2020)
The purpose of this study is to find out and describe how the impact of integrated one-stop service on malls in thecity of Manado. The research method used in this research is descriptive research method with a qualitativeapproach. Data collection in this study was carried out through interviews, observations and document collection.While the data analysis techniques that researchers use are qualitative with Miles and Huberman's descriptiveapproach. Based on the results of the study, it can be concluded that the One Stop On Mall Integrated ServicePolicy is an innovation and program that has a positive impact on the community in terms of licensing filemanagement from file entry to the stage of extraction/physical licensing, supported by satisfying and comfortablefacilities. the community and the online system that was put in place made the community satisfied with thepolicies issued by the Office of Investment and Integrated Services of the One Stop City of Manado. But inaddition to the positive impacts on the community there are also adverse impacts on the permit applicantcommunity, the lack of socialization of this public service center makes the community ignorance and causesintegrated one stop service on the mall to be quiet from the permit applicant, and the problem of coordinationbetween integrated onestop service Mantos and Integrated Services Policy in Manado City Tikala makes thecommunity who administer licenses at the center on mall services must take results / physical at the head office.The Impact of One Stop On Mall Integrated Services Policy makes the community and several related parties feelbenefited from this policy, for example the Mantos and local governments, the potential for more open economicdevelopment, then the flow of investment into the developer. In addition to receiving Local Revenue in this casethe local government (local government) through taxes for the region and a large amount of money for the localgovernment. In terms of speeding up and simplifying the administration of public service center licenses, this isthe right thing to be realized by the Integrated Services Policy in Manado City.Keywords : Policy Impact, Integrated One Stop Service On Mall